Meta-analysis of the efficacy and safety of Kanglaite Injection in conjunction with chemotherapy for cancer pain - Feng, Gaofei; Yi, Shujing; Chen, Ruo; Liu, Peng; Li, Yuanqi; Zhong, Yuantao; Peng, Zhaowen; Liu, Yufei; Xu, Shu (Frontiers in Oncology, 2026)
ObjectiveTo systematically assess the clinical efficacy and safety of Kanglaite Injection in combination with chemotherapy for cancer pain. Using PICO framework: Population (adult cancer patients with pain), Intervention (Kanglaite Injection + chemotherapy), Comparator (chemotherapy alone), Outcomes (pain scores, relief rates, KPS, adverse events).MethodsThe CNKI, WanFang, VIP, Chinese Biomedical Database, PubMed, Embase and Cochrane Library databases were systematically searched. Randomized controlled trials specifically investigating the combined use of Kanglaite Injection and chemotherapy for cancer pain were included from the inception of the database until October 14, 2025. Literature screening and quality assessment were independently conducted by two researchers, with cross-verification. The extracted data were meta-analyzed using Rev Man 5.3 software.ResultsA total of 18 randomized controlled trials involving 1197 patients were included. The combined analysis demonstrated that Kanglaite Injection in conjunction with chemotherapy showed significant advantages over chemotherapy alone in terms of pain intensity score [SMD=-1.24, 95% CI (-1.68, -0.80), P<0.001], pain relief rate [RR = 1.72, 95% CI (1.52, 1.95), P<0.001], and enhancement in the Karnofsky Performance Status (KPS) score improvement rate [RR = 1.64, 95% CI (1.39, 1.93), P<0.001]. Furthermore, Kanglaite Injection combined with chemotherapy exhibited advantages in reducing post-chemotherapy gastrointestinal reactions [RR = 0.68, 95% CI (0.57, 0.81), P<0.001], white blood cell reduction [RR = 0.73, 95% CI (0.57, 0.93), P<0.001], and liver function damage [RR = 0.45, 95% CI (0.27, 0.75), P<0.001]. Evidence certainty was moderate for most outcomes per GRADE assessment.ConclusionThe combination of Kanglaite Injection with chemotherapy appears effective and safe in treating cancer pain based on moderate-certainty evidence, pending further high-quality trials.